2005
DOI: 10.1080/14786430412331333374
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature precipitation in quenched Al–Cu–Mg alloys: a model for the reaction kinetics and yield strength development

Abstract: The microstructural evolution during low temperature ageing of two commercial purity alloys (Al-1.2Cu-1.2Mg-0.2Mn and Al-1.9Cu-1.6Mg-0.2Mn at.%) was investigated. The initial stage of hardening in these alloys is very rapid, with the alloys nearly doubling in hardness during 20 h ageing at room temperature. The microstructural evolution during this stage of hardening was investigated using differential scanning calorimetry (DSC), isothermal calorimetry and threedimensional atom probe analysis (3DAP). It is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 47 publications
13
122
1
Order By: Relevance
“…3D atom probe work has evidenced that in the present alloys room temperature hardening and hardening at 150 ºC is due to the formation of Cu-Mg coclusters [8,38,39], which become unstable at higher temperatures. Thus the endothermic effect up to about 230 to 250ºC is attributed mainly to the dissolution of these clusters [8,25,38]. For position 3, the dissolution of GPB2/S" phase will also contribute to the endothermic effect.…”
Section: Dsc Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…3D atom probe work has evidenced that in the present alloys room temperature hardening and hardening at 150 ºC is due to the formation of Cu-Mg coclusters [8,38,39], which become unstable at higher temperatures. Thus the endothermic effect up to about 230 to 250ºC is attributed mainly to the dissolution of these clusters [8,25,38]. For position 3, the dissolution of GPB2/S" phase will also contribute to the endothermic effect.…”
Section: Dsc Analysismentioning
confidence: 99%
“…The two main strengthening contributions to the strength variations across the weld are the increment in critical resolved shear stress (CRSS) due to co-clusters, Δτ cl , and the CRSS increment due to S phase precipitates, Δτ S . Detailed analysis of strengthening and composition of the co-clusters has revealed that Δτ cl ,can be approximated well as [8,26]:…”
Section: Heat Treatment -Microstructure -Strength Modelmentioning
confidence: 99%
See 3 more Smart Citations